2014
DOI: 10.1111/ped.12262
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Hashimoto's encephalopathy with peripheral nervous system involvement

Abstract: Hashimoto encephalopathy is a syndrome of encephalopathy associated with elevated concentration of circulating serum anti-thyroid antibodies usually responsive to steroid therapy. We report a 13-year-old girl with Hashimoto encephalopathy and peripheral nervous system involvement. The child had experienced high-grade pyrexia, global headache and sleeplessness. After admission she had an ileus with a distended urinary bladder, hallucinations and cognitive impairment. She had reduced deep tendon reflexes and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…13 To the best our knowledge, peripheral nerve involvement in HE was reported in only one case in the pediatric literature. Salpietro et al 16 reported a 13-year-old girl with HE who developed distal neuropathy. Her electromyography and nerve conduction velocity tests showed prolonged sensory latencies and reduced amplitude of action potentials in the upper and lower limbs segments with absent F-waves in the popliteal regions and the ankles bilaterally; motor conduction velocity was normal, indicating distal neuropathy (likely a polyneuropathy).…”
Section: Discussionmentioning
confidence: 99%
“…13 To the best our knowledge, peripheral nerve involvement in HE was reported in only one case in the pediatric literature. Salpietro et al 16 reported a 13-year-old girl with HE who developed distal neuropathy. Her electromyography and nerve conduction velocity tests showed prolonged sensory latencies and reduced amplitude of action potentials in the upper and lower limbs segments with absent F-waves in the popliteal regions and the ankles bilaterally; motor conduction velocity was normal, indicating distal neuropathy (likely a polyneuropathy).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiológicamente se estima una prevalencia de 2.1/100,000 casos 4 con una relación hombre/ mujer de 1:4, aunque puede afectar a jóvenes y niños 5,6 . Se asocia a otras patologías de condición autoinmune como la tiroiditis de Hashimoto, la hashitoxicosis, el síndrome de Sjögren, el lupus eritematoso sistémico, la enfermedad de Basedow 7 , la diabetes mellitus tipo 1, la sarcoidosis y la enfermedad de Biermer 8,9 .…”
Section: Discussionunclassified
“…10,17 This type of presentation is typical of childhood PTCS, and therefore it is important to exclude in patients with a possible underlying infectious and/or parainfectious process of the brain or spine and a postinflammatory torticollis. 29,30 Pulsatile tinnitus, also known as pulsesynchronous tinnitus, is another symptom of pediatric PTCS. 7,10 Pulsatile tinnitus is common in PTCS with and without papilledema and does not differ in its incidence between these two forms of PTCS.…”
Section: Clinical Assessment Of Pediatric Ptcsmentioning
confidence: 99%